Epithelial-Mesenchymal Transition in Asthma Airway Remodeling Is Regulated by the IL-33/CD146 Axis - Sun, Zhixiao; Ji, Ningfei; Ma, Qiyun; Zhu, Ranran; Chen, Zhongqi; Wang, Zhengxia; Qian, Yan; Wu, Chaojie; Hu, Fan; Huang, Mao; Zhang, Mingshun (Frontiers in Immunology, 2020)
Epithelial-mesenchymal transition (EMT) is essential in asthma airway remodeling. IL-33 from epithelial cells is involved in pulmonary fibrosis. CD146 has been extensively explored in cancer-associated EMT. Whether IL-33 regulates CD146 in the EMT process associated with asthma airway remodeling is still largely unknown. We hypothesized that EMT in airway remodeling was regulated by the IL-33/CD146 axis. House dust mite (HDM) extract increased the expression of IL-33 and CD146 in epithelial cells. Increased expression of CD146 in HDM-treated epithelial cells could be blocked with an ST2-neutralizing antibody. Moreover, HDM-induced EMT was dependent on the CD146 and TGF-β/SMAD-3 signaling pathways. IL-33 deficiency decreased CD146 expression and alleviated asthma severity. Similarly, CD146 deficiency mitigated EMT and airway remodeling in a murine model of chronic allergic airway inflammation. Furthermore, CD146 expression was significantly elevated in asthma patients. We concluded that IL-33 from HDM extract-treated alveolar epithelial cells stimulated CD146 expression, promoting EMT in airway remodeling in chronic allergic inflammation.